Human development and interaction in the age of ubiquitous technology - Rahman, Hakikur (© 2016 IGI Global, 2018)
This book was published in the IGI Global [© 2016 IGI Global] and the definite version is available at : http://doi.org/10.4018/978-1-5225-0556-3 The Journal's website is at: https://www.igi-global.com/gateway/book/147105